Evaluation of DHFR Inhibition and Antimicrobial Activity of Some Newly Synthesized Quinazolin-4(3H)-one Scaffold Coupled with Benzylidene and Ethylidene Amino Motifs - Harer, Sunil; Bhatia, Manish; Sonar, Priyanka (International Journal of Pharmaceutical Investigation)
Objectives: Substituted quinazolin-4(3H)-ones at position-3 with phenyl ring, heterocycles and aliphatic moieties, were reported to impart antimicrobial activities. In light of this, we have attempted to prepare a novel series of 2-pheny-3-substituted quinazolin-4(3H)-ones fused with an azomethine (-CH=N-) connection to Benzylidene and ethylidene motifs. Each of these motifs underwent testing to determine whether it could inhibit in-vitro microbial DHFR and the subsequent antimicrobial action. Materials and Methods: The synthesized 2-phenyl-3- substituted quinazolin-4(3H)-ones were characterized by FT-IR, 1H-NMR, 13C-NMR, ESI-MS and elemental (C, H, N, O and X=halogen) analysis. Evaluated results of in-vitro microbial DHFR inhibition are compared with the reported drug trimethoprim. Agar disc diffusion method was used for in-vitro antimicrobial activity, performed against pathogenic Gram-positive and Gram- negative bacteria like Staphylococcus aureus, Bacillus subtilis, and Escherichia coli, Pseudomonas aeruginosa respectively, and fungi like Candida albicans, and Aspergillus niger. Results: Docking analysis of ligands with DHFR (PDB=2W3M) has shown strong hydrophobic binding interaction and confirmed a perfect fit into the active domain of the target protein. Possible antimicrobial activity was induced from microbial DHFR inhibition. The results of the tests are compared with gentamycin, ciprofloxacin, and clotrimazole. Compounds with potent antibacterial activity were QI-j, and QII-f (MIC=0.1-0.2µg/mL), and moderately active compounds were QIa-d, QIl-m, QIII-d, and QIIIe-f (MIC=0.5-2.0µg/mL). Compounds exhibited potent antifungal activity were QI-c, QII-b, and QIII-f (MIC=0.1-0.2µg/mL), moderately active compounds were QIc-e, QI-g, QIm-n, QII-d, QIII-b, and QIII-e (MIC=0.5-2.0µg/mL). Conclusion: Particularly test compounds have produced DHFR inhibition in a range of 4-24µM as compared with trimethoprim (IC50=10 µM). Benzylidene and ethylidene moieties attached to the quinazolin-4(3H)-one had contributed to this activity. Present series of substituted quinazolin-4(3H)-ones provide a path for the design and development of newer antimicrobial agents in the treatment of deadly pathogenic infections.
Keywords: Quinazolin-4(3H)-ones; Antimicrobial activity; MIC; DHFR; IC50; Docking analysis.